Rare-Earth-Metal-Catalyzed Regioselective Hydrosilylation of Internal Alkenes and Alkynes - Zhu, Chenhao; Mao, Tao; Feng, Xiaoming; Dong, Shunxi (Synthesis, 2024)
A highly regioselective hydrosilylation reaction of internal alkenes was achieved by using commercially available lanthanum hexamethyldisilazane (La(HMDS)3). Notably, the Z- or E-configuration of internal alkenes has negligible influence on either the reactivity or regioselectivity. Internal alkynes could also be used, affording the mono di-hydrosilylation product in the presence of La(HMDS)3 or mono-hydrosilylation product with Y(HMDS)3 as the promoter.
Keywords: hydrosilylation; internal alkenes; internal alkynes; rare-earth metals; regioselectivity